Nursing students' perceptions of using the Clinical Education Assessment tool AssCE and their overall perceptions of the clinical learning environment - A cross-sectional correlational study. (April 2017) - Engström, Maria; Löfmark, Anna; Vae, Karen Johanne Ugland; Mårtensson, Gunilla
Abstract: Background: Clinical education is a vital part of nursing students' learning; the importance of assessment tools and feedback in stimulating student learning has been stressed, but this needs to be studied in more detail. Objectives: To examine relationships between nursing students' perceptions of using an Assessment tool in Clinical Education (AssCE) during their mid-course discussion and final assessment, the content discussed during these meetings between the student, preceptor and nurse teacher and the students' overall perception of the clinical learning environment. Design: A cross-sectional, correlational design was used. Setting and Participants: A convenience sample of 110 nursing students from one Norwegian university college with two campuses. Methods: Data were collected with self-developed questionnaires and analysed using logistic regression with SPSS and the PROCESS macro for mediation analysis. Results: There was a positive relationship between nursing students' perceptions of using the assessment tool AssCE and their overall perception of the clinical learning environment. This relationship was, in turn, mediated by the content discussed during the formative mid-course discussion and summative final assessment. Conclusions: Our conclusion is that the assessment tool AssCE supported students' clinical learning and that this relationship, in turn, was mediated by the degree to which the conversation during the assessment meeting focused on the student's knowledge, skills and professional judgement. Highlights: The use of an assessment tool and its significance for students' perception of the clinical learning environment. The importance of level and content in the assessment discussion; to discuss knowledge, skills and professional judgement. The need for a reflective practice, by receiving feedback, to enhance students' learning.